Single Prazosin Infusion in Prelimbic Cortex Fosters Extinction of Amphetamine-Induced Conditioned Place Preference - Latagliata, Emanuele C.; Lo Iacono, Luisa; Chiacchierini, Giulia; Sancandi, Marco; Rava, Alessandro; Oliva, Valeria; Puglisi-Allegra, Stefano (Frontiers in Pharmacology, 2017)
Exposure to drug-associated cues to induce extinction is a useful strategy to contrast cue-induced drug seeking. Norepinephrine (NE) transmission in medial prefrontal cortex has a role in the acquisition and extinction of conditioned place preference induced by amphetamine. We have reported recently that NE in prelimbic cortex delays extinction of amphetamine-induced conditioned place preference (CPP). A potential involvement of α1-adrenergic receptors in the extinction of appetitive conditioned response has been also suggested, although their role in prelimbic cortex has not been yet fully investigated. Here, we investigated the effects of the α1-adrenergic receptor antagonist prazosin infusion in the prelimbic cortex of C57BL/6J mice on expression and extinction of amphetamine-induced CPP. Acute prelimbic prazosin did not affect expression of amphetamine-induced CPP on the day of infusion, while in subsequent days it produced a clear-cut advance of extinction of preference for the compartment previously paired with amphetamine (Conditioned stimulus, CS). Moreover, prazosin-treated mice that had extinguished CS preference showed increased mRNA expression of brain-derived neurotrophic factor (BDNF) and post-synaptic density 95 (PSD-95) in the nucleus accumbens shell or core, respectively, thus suggesting that prelimbic α1-adrenergic receptor blockade triggers neural adaptations in subcortical areas that could contribute to the extinction of cue-induced drug-seeking behavior. These results show that the pharmacological blockade of α1-adrenergic receptors in prelimbic cortex by a single infusion is able to induce extinction of amphetamine-induced CPP long before control (vehicle) animals, an effect depending on contingent exposure to retrieval, since if infused far from or after reactivation it did not affect preference. Moreover, they suggest strongly that the behavioral effects depend on post-treatment neuroplasticity changes in corticolimbic network, triggered by a possible “priming” effect of prazosin, and point to a potential therapeutic power of the antagonist for maladaptive memories.